INNOVATIVE FOUNDATIONS OF A UNIFIED ECONOMY IN THE FIELD OF RELIGIOUS EDUCATION - Bobojonova Zarnigor Shokirovna; Xurramov Shohboz Xurram o’g’li (Western European Studies, 2024)
this article highlights theoretical views on the need to manage, on the basis of new economic views, economic processes that are becoming more complex in the conditions of world economic globalization.
Keywords: unified economy; innovative competence; economic harmony